Theological Foundation: The Apostle Paul and his Framework of thinking - David Ming (International Journal of Indonesian Philosophy & Theology, 2023)
The author identifies several related problems in this scientific work. These problems are evident from the points that have been compiled as follows: First, there are indications that some Christians themselves think that evangelism is only a social activity or just a good life behaviour in society. Second, there are indications that most of our evangelism is direct evangelism. Third, there are indications that not all Christians are passionate about sharing the gospel. The author sees the danger in contextualization: “If contextualization is not carried out, theology will not be relevant; and the same danger is that if contextualization is carried out too vigorously, compromise and syncretism will occur. It is hoped that this research can be input for Christian educators, pastors, and elderly congregations to implement an evangelistic lifestyle under 1 Corinthians 9:1-27 and call the churches to follow him as he followed Christ. Furthermore, it is hoped that this research can be input for Christian educators, pastors, and elderly congregations in implementing an evangelistic lifestyle.